2020
DOI: 10.3390/cryst10070620
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Surface Morphology Effect on the Cytotoxicity of [Al2O3/ZnO]n/316L SS Nanolaminates Growth by Atomic Layer Deposition (ALD)

Abstract: Recently, different biomedical applications of aluminum oxide (Al2O3) and zinc oxide (ZnO) have been studied, and they have displayed good biocompatible behavior. For this reason, this study explores nanolaminates of [Al2O3/ZnO]n obtained by atomic layer deposition (ALD) on silicon (100) and 316L stainless steel substrates with different bilayer periods: n = 1, 2, 5, and 10. The intention is to correlate the structure, chemical bonds, morphology, and electrochemical properties of ZnO and Al2O3 single layers an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The Al2O3 / ZnO nanolaminates exhibited a modulus of 140 to 145 GPa, which lies in between the value for the two films, and a hardness of 8 GPa, which is similar to that of Al2O3. Osorio et al [41] examined the electrochemical behavior of these nanolaminates on 316L SS. Their results showed that the corrosion resistance of [Al2O3/ZnO]n nanolaminates was higher in comparison with single layered 316L SS surface.…”
Section: Introductionmentioning
confidence: 99%
“…The Al2O3 / ZnO nanolaminates exhibited a modulus of 140 to 145 GPa, which lies in between the value for the two films, and a hardness of 8 GPa, which is similar to that of Al2O3. Osorio et al [41] examined the electrochemical behavior of these nanolaminates on 316L SS. Their results showed that the corrosion resistance of [Al2O3/ZnO]n nanolaminates was higher in comparison with single layered 316L SS surface.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, ZnO, in both the single‐layer and NL TFEs, crystallizes in a wurtzite‐type structure. [ 31 ] The single‐layer ZnO is polycrystalline with peaks at 31.3°, 34.75°, 37°, and 47.30°, corresponding to the (100), (002), (101), and (102) planes, respectively. [ 32 ] For the 2‐layer NL TFE, the intensity of the ZnO peaks decreased slightly compared to the single‐layer ZnO, as the ZnO layer is thinner.…”
Section: Resultsmentioning
confidence: 99%
“…First, the use of ALD-based metal oxide chemistries such as Al 2 O 3 , ZnO, and TiO 2 are well established. A key advantage being that ALD occurs at relatively low temperatures (≤150 °C) to maintain the API’s viability. Second, the metal oxide candidates presented above are considered biocompatible and present no known toxicity. Third, ALD provides non-line-of-sight and self-limiting deposition characteristics that result in highly conformal and pin-hole free films that act as diffusion barriers around particles . Fourth, the use of nanoscale films to coat API powders provides flexibility in terms of adding multifunctionality to pills without adding to its bulk and thus can result in maintaining high dosage levels.…”
Section: Introductionmentioning
confidence: 99%